Optimalisasi Program 7 Jurus BK Hebat melalui Psikoedukasi Mindful Teaching bagi Guru BK di Kota Palu [Optimization of the "7 Jurus BK Hebat" Program through Mindful Teaching Psychoeducation for Guidance and Counseling Teachers in Palu City] - Dhevy Puswiartika; Bau Ratu; Nurwahyuni Nurwahyuni; Ikhlas Rasido; Munifah Munifah; Micha Felayati Silalahi (Indonesia Berdaya, 2026)
This psychoeducation program, focusing on the topic of Mindful Teaching, aims to enhance the understanding and skills of Guidance and Counseling (BK) teachers regarding the use of mindfulness techniques to optimize the implementation of the "7 Jurus BK Hebat" program. The methods utilized in this psychoeducation included lectures, demonstrations, and practical exercises. The program consisted of two sessions. The agenda for the first session comprised material presentation regarding the basic concepts of mindfulness and mindful teaching, as well as the urgency of mindfulness techniques in the learning process as an effort to optimize the "7 Jurus BK Hebat" program. Subsequently, the second session involved the introduction of various mindfulness techniques, followed by demonstrations and practices of techniques such as mindful breathing, mindful chair yoga, mindful eating, and mindful reading. This psychoeducation activity was conducted in a hybrid format, involving 30 Guidance and Counseling teachers from junior and senior high schools (SMP and SMA/SMK) in Palu City. The participants engaged in this psychoeducation program with enthusiasm and high spirits. They expressed readiness to apply these mindfulness techniques in their daily lives as educators and counselors to optimize the "7 Jurus BK Hebat" program in schools. Abstrak. Program psikoedukasi dengan topik Mindful Teaching ini bertujuan untuk meningkatkan pemahaman dan keterampilan guru BK terkait penggunaan teknik mindfulness untuk mengoptimalkan implementasi program 7 Jurus BK Hebat. Metode yang digunakan dalam psikoedukasi ini, meliputi: ceramah, demonstrasi, dan praktik. Program psikoedukasi terdiri dari dua sesi. Agenda sesi pertama berupa pemaparan materi terkait konsep dasar mindfulness dan mindful teaching, dan urgensi teknik mindfulness dalam proses pembelajaran sebagai upaya mengoptimalkan program 7 Jurus BK Hebat. Selanjutnya, agenda sesi kedua berupa pengenalan berbagai macam teknik mindfulness, dilanjutkan dengan demonstrasi dan latihan teknik mindfulness, seperti: mindful breathing, mindful chair yoga, mindful eating, dan mindful reading. Kegiatan psikoedukasi ini dilaksanakan secara hybrid dengan melibatkan partisipan sejumlah 30 orang guru Bimbingan dan Konseling yang mengajar di SMP dan SMA/SMK di Kota Palu. Para peserta telah mengikuti program psikoedukasi ini dengan antusias dan semangat. Mereka juga siap menerapkan teknik mindfulness ini dalam kehidupan sehari-hari sebagai pengajar dan konselor sebagai upaya optimalisasi program 7 Jurus BK Hebat di sekolah.